Search Costs and Diminishing Sensitivity - Heiko Karle; Florian Kerzenmacher; Heiner Schumacher; Frank Verboven (Center for Economic Studies and ifo Institute (CESifo), 2022)
Empirical search cost estimates tend to increase in the size of the transaction, even if search can be done conveniently online. To assess this pattern systematically, we conduct an online search experiment in which we manipulate the price scale while keeping the physical search effort for each price quote constant. Based on a standard search model, we confirm that search cost estimates indeed increase considerably in the price scale. We then modify the search model to allow for diminishing sensitivity, i.e., the tendency that people become less sensitive to price variations of fixed size when the price of the good increases. With the modified model, we find substantial degrees of diminishing sensitivity and obtain search cost estimates that are scale-independent. We show that these search cost estimates correspond well to subjects' true opportunity costs of time and that the consumer welfare loss from diminishing sensitivity can be quite substantial.
Keywords: C90; D12; D83; 330; consumer search; diminishing sensitivity; search costs